Karunairajah A/L Rasiah V Punithambigai A/P Ponniah: The Need To Amend Section 95 Of The Law Reform (Marriage And Divorce) Act 1976? - Thambapillay, Sridevi (Journal of Malaysian and Comparative Law, 2005)
The recent Federal Court decision in Karunairajah A/L Rasiah V Punithambigai A/P Ponniah (hereafter referred to as "the present case") could be described as one that has shattered the hopes of children above the age of 18 years who are financially dependent on their divorced parents for the purpose of completing their tertiary education. Their hopes were raised by the Court of Appeal’s decision in the case of Ching Seng Woah v Lim Shook Lin, which was followed by the High Court and the Court of Appeal in the present case. In Ching Seng Woah v Lim Shook Lin, the Court held that the involuntary financial dependence of a child of the marriage for the purpose of pursuing and/or completing tertiary and/or vocational education came within the exception of physical or mental disability under section 95 of the Law Reform (Marriage and Divorce) Act 1976 (hereinafter referred to as "the LRA") so as to entitle the child to maintenance beyond the age of 18 years. Section 95 of the LRA stipulates as follows: Except where an order for custody or maintenance of a child is expressed to be for any shorter period or where any such order has been rescinded, it shall expire on the attainment by the child of the age of eighteen years or where the child is under physical or mental disability, on the ceasing of such disability, whichever is the later. The objective of this article is to examine whether there is a need to amend section 95 of the LRA in light of the Federal Court decision in Karunairajah A/L Rasiah V Punithambigai A/P Ponniah. The writer intends to achieve this objective by reviewing the decisions of the High Court, Court of Appeal and the Federal Court in the present case.